Hubungan Postpartum Blues dengan Kualitas Hidup pada Ibu Nifas di Denpasar - Parwati, Ni Wayan Manik; Haryati, Ni Putu Sri; Wulandari, Idah Ayu; Gayatri, Ni Luh Putu (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2024)
Women who have finished giving birth will enter the puerperium. There are several types of disorders that occur during this period, one of which is postpartum blues. The postpartum period can change several characteristics of the mother such as psychological conditions, emotional, social, sexual and spiritual changes. This is experienced by all postpartum mothers and is unique in the critical complex period including quality of life. The purpose of this study was to determine the relationship between postpartum blues and quality of life in postpartum mothers. This research is a correlation analytic study with a cross sectional design. This research was conducted in the city of Denpasar in the month August-October 2022.The population in this study were all postpartum mothers in Denpasar City using cluster sampling. The data collection tool used in this study was a questionnairestandard developed by Cox, et.al. namely the Edinburgh Postnatal Depression Scale (EPDS). The data that has been collected is tested for normality with the Kolmogorov-Smirnov test with a p value <0.05 so that the data is not normally distributed. Test using Spearman's rho non-parametric statistical test. The results and conclusions in this study were obtained P value <0.001 and r = -744 which indicates that there is a close relationship between postpartum blues and the quality of life of postpartum women.